Knowledge-based capital and productivity divergence - Marie Le Mouel; Alexander Schiersch (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Understanding the causes of the slowdown in aggregate productivity growth is key to maintaining the competitiveness of advanced economies and ensuring long-term economic prosperity. This paper is the first to provide evidence that investment in Knowledge-Based Capital (KBC), despite having a positive effect on productivity at the micro level, is a driver of the weak productivity performance at the aggregate level, by accentuating divergence between a group of "frontier" firms and the rest of the economy. Using detailed firm-level administrative data for Germany, we find evidence that the effect of KBC on productivity is heterogeneous across firms within industries: this effect is 3 times larger for firms in the top quintile of the KBC distribution compared to firms in the bottom quintile of the KBC distribution. We document the existence of divergence in productivity growth between top KBC users and the rest of firms at the industry level, and find that industries where this gap is larger are also those industries where the heterogeneity in the effect of KBC is highest and where average productivity growth was lower. The evidence hence supports the view that the use of KBC plays a role in explaining weak productivity growth, by accentuating differences between firms.
Keywords: D24; L25; O14; O30; O47; 330; Knowledge-Based Capital; Firm dynamics; Productivity divergence